Cardiac Ischemic Preconditioning Promotes MG53 Secretion Through H2O2-Activated Protein Kinase C-δ Signaling. Issue 11 (15th September 2020) - Shan, Dan; Guo, Sile; Wu, Hong-Kun; Lv, Fengxiang; Jin, Li; Zhang, Mao; Xie, Peng; Wang, Yimei; Song, Ying; Wu, Fujian; Lan, Feng; Hu, Xinli; et al.
Abstract : Background: Ischemic heart disease is the leading cause of morbidity and mortality worldwide. Ischemic preconditioning (IPC) is the most powerful intrinsic protection against cardiac ischemia/reperfusion injury. Previous studies have shown that a multifunctional TRIM family protein, MG53 (mitsugumin 53; also called TRIM72), not only plays an essential role in IPC-mediated cardioprotection against ischemia/reperfusion injury but also ameliorates mechanical damage. In addition to its intracellular actions, as a myokine/cardiokine, MG53 can be secreted from the heart and skeletal muscle in response to metabolic stress. However, it is unknown whether IPC-mediated cardioprotection is causally related to MG53 secretion and, if so, what the underlying mechanism is. Methods: Using proteomic analysis in conjunction with genetic and pharmacological approaches, we examined MG53 secretion in response to IPC and explored the underlying mechanism using rodents in in vivo, isolated perfused hearts, and cultured neonatal rat ventricular cardiomyocytes. Moreover, using recombinant MG53 proteins, we investigated the potential biological function of secreted MG53 in the context of IPC and ischemia/reperfusion injury. Results: We found that IPC triggered robust MG53 secretion in rodents in vivo, perfused hearts, and cultured cardiac myocytes without causing cell membrane leakage. Mechanistically, IPC promoted MG53 secretion through H2 O2 -evoked activation of protein kinase-C-δ. Specifically, IPC-induced myocardial MG53 secretion was mediated by H2 O2 -triggered phosphorylation of protein kinase-C-δ at Y311, which is necessary and sufficient to facilitate MG53 secretion. Functionally, systemic delivery of recombinant MG53 proteins to mimic elevated circulating MG53 not only restored IPC function in MG53-deficient mice but also protected rodent hearts from ischemia/reperfusion injury even in the absence of IPC. Moreover, oxidative stress by H2 O2 augmented MG53 secretion, and MG53 knockdown exacerbated H2 O2 -induced cell injury in human embryonic stem cell–derived cardiomyocytes, despite relatively low basal expression of MG53 in human heart. Conclusions: We conclude that IPC and oxidative stress can trigger MG53 secretion from the heart via an H2 O2 –protein kinase-C-δ–dependent mechanism and that extracellular MG53 can participate in IPC protection against cardiac ischemia/reperfusion injury. Abstract : Supplemental Digital Content is available in the text.